If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 * 2x + 5 = 102 Multiply -3 * 2 4x + -6x + 5 = 102 Reorder the terms: 5 + 4x + -6x = 102 Combine like terms: 4x + -6x = -2x 5 + -2x = 102 Solving 5 + -2x = 102 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 102 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 102 + -5 -2x = 102 + -5 Combine like terms: 102 + -5 = 97 -2x = 97 Divide each side by '-2'. x = -48.5 Simplifying x = -48.5
| x/675=(825-x)/350 | | 36=-4(2x-3) | | 2x(3-4)=4(5-x) | | x+3/2=x | | 6u^2+5u-3=0 | | 3/5x+11=21 | | 5(1+f)+8=3(f-1) | | 4y^2-31y+21= | | 269-4x=41x+24x | | 7-8x=152-43x | | x^2-3x=13 | | 2c(3b-4)-3b(-5+2c)= | | 6w^2+11w+3=0 | | 10-10x=1333-31x | | 1/4x2/4 | | 2k^2-7k-15=0 | | 5x+3=4x-4 | | z^2-z+5=0 | | 4(2-4x)=16 | | 3x=22x | | 3ix-5+3i=(3-1)y+1 | | 7m-2m= | | 53-2x=25x+20 | | 6x+129=16x-11 | | 8-10=2x | | 4u^2+23u+28=0 | | 10x+2=8x+14 | | -2x+4=-4x+2 | | (2x^2y-3y^4)dx+(3x^3+2xy^3)dy=0 | | (2x^2y-3y^4)dx+(3x^3-2xy^3)dy=0 | | 4x+2=-2x+7 | | -3x+7=4x-12 |